Tomato gynoecium patterning and fruit development are orchestrated by the interplay between microRNAs and gibberellin - Corrêa, João Paulo de Oliveira (2019)
Many characteristics of a fully developed fruit are controlled by processes that take place early in fruit development, even at floral meristem level. In fact, events that range from the transition of a vegetative into an inflorescence meristem to the last stages of fruit ripening determine characteristics of a mature fruit. Transcription factors post-transcriptionally regulated by microRNAs (miRNAs) play crucial roles in most of these stages. In such pathways, miRNAs may regulate its targets spatially, temporally, or dampen amount of targets transcript to provide optimal expression patterns for adequate organ development. Many miRNAs have been described to be essential in the regulation of flowering time, gynoecium patterning, post-pollination gynoecium growth and fruit ripening, among other stages of fruit development. Some aspects of early stages of gynoecium development, such as floral meristem maintenance, carpel fusion and gynoecium pattern, have been well studied in Arabidopsis. However, these stages are poorly understood in the development of fleshy fruit species, such as tomato. Many miRNA-related pathways were described to interact with phytohormone pathways. A good example is the interaction between miR156 and Gibberellins (GA) in the regulation of flowering time. Interestingly, this interaction is substantially different in Arabidopsis and tomato. MiR156 have been also shown to have distinct roles in controlling tomato and Arabidopsis gynoecium development. Considering this, here we: (1) review the available literature concerning control of fruit development, from gynoecium patterning to fruit ripening, by non-coding RNAs and (2) study the relationship between miR156 and GA pathways in the regulation of early stages of fruit development. We show that these pathways control floral meristem size and boundary establishment during gynoecium development and miR156 pathway modulates responses to GA.